Factors Affecting the Independence of Women in Home Industry in Facing the Covid Pandemic in Pandeglang Regency (Case of the Female Emping Melinjo Craftsman) - Khaerul Saleh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The existence of the COVID-19 pandemic that hit parts of the world at a macro level devastated the economic system, both large economies and the home economy were also affected by this event. This study aims to determine (1) the factors that influence the independence of women in home industry, and (2) the dominant factors that influence the independence of women in the home industry in Pandeglang Regency due to covid 19. This research was carried out in Pandeglang Regency with 152 respondents. all of which are women who run the melinjo emping home industry on a daily basis. The research design uses an explorative design. The types of data used are qualitative data and quantitative data. The subject of the research is a cottage industry managed by rural women, and the object is the independence factor of the cottage industry. The data needed in this study are data on family support, access to capital, entrepreneurial ability, and business scale, as well as internal factors and social networks, government support and access to information as external factors. The results showed that the independence of women home industry players in Pandeglang Regency during the Covid 19 pandemic was in the moderate category, there were two factors that influenced the independence of women in the home industry in Pandeglang Regency, namely: (1) internal factors, and (2) external factors. The most dominant factors influencing the independence of women in the home industry in Pandeglang Regency are internal factors, which include: business scale, access to capital, and business ability, while external factors that influence include others; social networks and access to information. Meanwhile, government support and family support have little effect on the independence of women in home industry in Pandeglang Regency.